A direct injection technique for investigation of lung sensory properties and reflex functions. Issue 7 (29th May 2021) - Walker, Jerome F.; Yu, Jerry
Abstract : New Findings: This article reviews a unique direct injection technique that complements the more conventional right atrial injection and aerosol delivery methods to study sensory and reflex effects of the lung sensors. Used in combination with other methods, this technique should contribute to the pulmonary sensory research. Abstract: The lungs house sensory receptors (sensors) that mediate a variety of sensory and reflex responses to mechanical or chemical changes. These reflexes are mainly carried through pulmonary sympathetic and vagal afferent pathways. The chemosensors in the lung periphery are especially important in pulmonary diseases and their reflex responses have traditionally been studied either by aerosol delivery, which also activates receptors in the central airways, or by right atrial injection, which also activates receptors lying outside the lung. Thus, these techniques may confound the interpretation of sensory function. Our laboratory has developed a direct injection technique to deliver agents into the lung parenchyma, which complements the conventional techniques with some important advantages. This article reviews the technique. Abstract :